Navigating Moral Struggle: Toward a Social Model of Exemplarity. Issue 3 (16th August 2019) - Hamilton, Brian
Abstract: Exemplars have the power to help people navigate various levels of moral struggle, from the relatively straightforward problem of lacking motivation to the much deeper problem of failing to see the moral realities that surround us. But there are also serious moral risks in the appeal to exemplars: we romanticize them, we make use of them in authoritarian ways, and we tend to forget how our choice of exemplars is conditioned by oppressive cultural formations. I argue that we need to develop a social model of exemplarity, attuned to social contexts of our exemplars themselves as well as the social processes of constructing and appealing to exemplars. More particularly, I argue that we need to develop space for thinking about exemplary groups, not just exemplary individuals, in order to develop the strengths and avoid the weaknesses in exemplarist moral theories.